The spectral applications of Beer-Lambert law for some biological and dosimetric materials - Icelli, Orhan; Yalcin, Zeynel; Karakaya, Vatan; Ilgaz, Isil P. (AMER INST PHYSICS, 2014)
The aim of this study is to conduct quantitative and qualitative analysis of biological and dosimetric materials which contain organic and inorganic materials and to make the determination by using the spectral theorem Beer-Lambert law. Beer-Lambert law is a system of linear equations for the spectral theory. It is possible to solve linear equations with a non-zero coefficient matrix determinant forming linear equations. Characteristic matrix of the linear equation with zero determinant is called point spectrum at the spectral theory.
Keywords: Beer-lambert law; Spectral theory; Point; Continuous; Residual spectrum; Mathematics; Physics